HerStory : iconic women of history [games] - Bentley, Nick; Reynolds, Danielle; Matsuuchi, Emerson (Underdog Games, 2022)
"In HerStory, you're an acclaimed author, writing a book to tell the stories of remarkable women of history. The players take turns doing research, drafting chapters, and completing them, for points. The game ends when a player has written 8 chapters, and the player with the highest-scoring book wins!" -- Container.